Assessment and management of constipation for patients receiving palliative care in specialist palliative care settings: A systematic review of the literature. (May 2018) - Muldrew, Deborah HL; Hasson, Felicity; Carduff, Emma; Clarke, Mike; Coast, Jo; Finucane, Anne; Graham, Lisa; Larkin, Philip; McCorry, Noleen K.; Slater, Paul; Watson, Max; Wright, Eileen; et al.
Background: Constipation is an important issue for patients receiving palliative care within specialist palliative care settings. Questions and ambiguity, however, persist about international best practice and management. Aim: To synthesise the current evidence base on the assessment and management of constipation for palliative care patients within a specialist palliative care setting. Design: This is a systematic review. Data sources: MEDLINE, Embase, CINAHL, Scopus and Cochrane databases were systematically searched in April 2017 for empirical studies, written in English, on the assessment and management of constipation in specialist palliative care settings, published between 2007 and 2017. Two researchers independently reviewed and critically appraised all studies, conducted data extraction, and undertook a thematic analysis. Results: In total, 13 studies were included in the review comprising randomised trials ( n = 3), observational ( n = 4) and descriptive studies ( n = 6). Most research was conducted in specialist palliative care units, targeting either healthcare professionals or patients. The analysis highlighted a lack of standard definition of constipation, raising questions on the existence and comparability of baseline prevalence figures, the physical and psychological impact on patients, resource impact on staff and service, the subjective and objective methods of assessing constipation, and key aspects of constipation management, including a lack of focus on non-pharmacological management in this setting. Conclusion: The results of this review are being used to inform the development of an educational intervention targeting healthcare professionals. Gaps in the evidence base include lack of consistent definition of constipation, constipation prevention, non-pharmacological management, and the consideration of the management of constipation for the dying patient.